Prenatal music exposure induces long-term neural effects. - Eino Partanen (Public Library of Science (PLoS), 2013)
We investigated the neural correlates induced by prenatal exposure to melodies using brains' event-related potentials (ERPs). During the last trimester of pregnancy, the mothers in the learning group played the 'Twinkle twinkle little star'-melody 5 times per week. After birth and again at the age of 4 months, we played the infants a modified melody in which some of the notes were changed while ERPs to unchanged and changed notes were recorded. The ERPs were also recorded from a control group, who received no prenatal stimulation. Both at birth and at the age of 4 months, infants in the learning group had stronger ERPs to the unchanged notes than the control group. Furthermore, the ERP amplitudes to the changed and unchanged notes at birth were correlated with the amount of prenatal exposure. Our results show that extensive prenatal exposure to a melody induces neural representations that last for several months.